Large-area few-layer MoS2 deposited by sputtering. (6th June 2016) - Huang, Jyun-Hong; Chen, Hsing-Hung; Liu, Pang-Shiuan; Lu, Li-Syuan; Wu, Chien-Ting; Chou, Cheng-Tung; Lee, Yao-Jen; Li, Lain-Jong; Chang, Wen-Hao; Hou, Tuo-Hung
Abstract: Direct magnetron sputtering of transition metal dichalcogenide targets is proposed as a new approach for depositing large-area two-dimensional layered materials. Bilayer to few-layer MoS2 deposited by magnetron sputtering followed by post-deposition annealing shows superior area scalability over 20 cm 2 and layer-by-layer controllability. High crystallinity of layered MoS2 was confirmed by Raman, photo-luminescence, and transmission electron microscopy analysis. The sputtering temperature and annealing ambience were found to play an important role in the film quality. The top-gate field-effect transistor by using the layered MoS2 channel shows typical n-type characteristics with a current on/off ratio of approximately 10 4 . The relatively low mobility is attributed to the small grain size of 0.1–1 μ m with a trap charge density in grain boundaries of the order of 10 13 cm –2 .